Utilizing Nanoparticles to Overcome Anti-PD-1/PD-L1 Immunotherapy Resistance in Non-Small Cell Lung cancer: A Potential Strategy - Ge Y; Zhou Q; Pan F; Wang R (International Journal of Nanomedicine)
Yuli Ge,1 Qiong Zhou,2 Fan Pan,2 Rui Wang1 1Department of Medical Oncology, Jinling Clinical Medical College, Nanjing University of Chinese Medicine, Nanjing, Jiangsu, 210023, People’s Republic of China; 2Department of Medical Oncology, Nanjing Jinling Hospital, Affiliated Hospital of Medical School, Nanjing University, Nanjing, Jiangsu, 210093, People’s Republic of ChinaCorrespondence: Rui Wang, Department of Medical Oncology, Jinling Clinical Medical College, Nanjing University of Chinese Medicine, Nanjing, Jiangsu, 210023, People’s Republic of China, Email wangrui218@163.comAbstract: Lung cancer is the leading cause of cancer-related mortality globally, with non-small cell lung cancer (NSCLC) constituting 85% of cases. Immune checkpoint inhibitors (ICIs) represented by anti-programmed cell death protein 1 (PD-1)/ programmed cell death ligand 1 (PD-L1) have emerged as a promising frontier in cancer treatment, effectively extending the survival of patients with NSCLC. However, the efficacy of ICIs exhibits significant variability across diverse patient populations, with a substantial proportion showing poor responsiveness and acquired resistance in those initially responsive to ICIs treatments. With the advancement of nanotechnology, nanoparticles offer unique advantages in tumor immunotherapy, including high permeability and prolonged retention(EPR) effects, enhanced drug delivery and stability, and modulation of the inflammatory tumor microenvironment(TME). This review summarizes the mechanisms of resistance to ICIs in NSCLC, focusing on tumor antigens loss and defective antigen processing and presentation, failure T cell priming, impaired T cell migration and infiltration, immunosuppressive TME, and genetic mutations. Furthermore, we discuss how nanoparticles, through their intrinsic properties such as the EPR effect, active targeting effect, shielding effect, self-regulatory effect, and synergistic effect, can potentiate the efficacy of ICIs and reverse resistance. In conclusion, nanoparticles serve as a robust platform for ICIs-based NSCLC therapy, aiding in overcoming resistance challenges.Keywords: PD-1/PD-L1, immunotherapy, resistance mechanisms, immunosuppression TME, nanoparticles, pro-inflammatory TME